PECVD법에 의해 증착된 Ti-B-C 코팅막 내의 보론함량과 증착온도에 따른 미세구조 및 기계적 물성의 변화 - 옥정태(Jung Tae Ok); 송풍근(Pung Keun Song); 김광호(Kwang Ho Kim) (Biuletyn Uniejowski, 2005)
Ternary Ti-B-C coatings were synthesized on WC-Co and Si wafers substrates by a PECVD technique using a gaseous mixture of $TiCl_4,\;BCl_3,\;CH_4,\;Ar,\;and\; H_2$. The effects of deposition variables such as substrate temperature, gas ratio, $R_x=[BCl_3/(CH_4+BCl_3)]$ on the microstructure and mechanical properties of Ti-B-C coatings were investigated. From our instrumental analyses, the synthesized Ti-B-C coatings was confirmed to be composites consisting of nanocrystallites TiC, quasi-amorphous TiB2, and amorphous carbon at low boron content, on the contrary, nanocrystallites $TiB_2$, quasi-amorphous TiC, and amorphous carbon at relatively high boron content. The microhardness of the Ti-B-C coatings increased from $\~23 GPa$ of TiC to $\~38 GPa$ of $Ti_{0.33}B_{0.55}C_{0.11}$ coatings with increasing the boron content. The $Ti_{0.33}B_{0.55}C_{0.11}$ coatings showed lower average friction coefficient of 0.45, in addition, it showed relatively better wear behavior compared to other binary coatings of $TiB_2$ and TiC. The microstruture and microhardness value of Ti-B-C coatings were largely depend on the deposition temperature.